Color changing bioadhesive barrier for peripherally inserted central catheters - Djordjevic, Ivan (2024)
Bacteria migration at catheter insertion sites presents a serious complication (bacteraemia) with high mortality rates. One strategy to mediate bacteraemia is a physical barrier at the skin-catheter interface. Herein a colorimetric biosensor adhesive (CathoGlu) is designed and evaluated for both colorimetric detection of bacterial infection and application as a bacteria barrier. The design intent combines viscous, hydrophobic bioadhesive with an organic pH indicator (bromothymol blue). Visual observation can then distinguish healthy skin at pH = ~5 from an infected catheter insertion site at pH = ~8. The liquid-to-biorubber transition of CathoGlu formulation occurs via a brief exposure to UVA penlight, providing an elastic barrier to the skin flora. Leachates from CathoGlu demonstrate no genotoxic and skin sensitization effect, assessed by OECD-recommended in vitro and in chemico assays. The CathoGlu formulation was found non-inferior against clinically approved 2-octyl-cyanoacrylate (DermabondTM), and adhesive tape (MicroporeTM) within an in vivo porcine model. CathoGlu skin adhesive provides new opportunities to prevent sepsis in challenging clinical situations.